(untitled) (Politeja, 2022)
„Misleading analogy”: About Differences Between Referendum in Scotland and Catalonia Separatist aspirations in Europe are now a captivating issue. Regions like Scotland and Catalonia deserve special attention. The aim of the article is to show differences in the perception of both cases, due to their frequent comparing in journalistic papers. The study consists of two parts that concern Scotland and Catalonia. In each of them the institutional and legal positions of the regions were taken into the consideration. In addition, the course of events in Scotland and Catalonia in 2014 and 2017 was considered in the context of the independence referendums carried out in these regions. The summary of this article consists of comparison of the factors which show that there are no grounds for adapting analogy between Scotland and Catalonia. Factors that have been taken into account are: the legal order and the regulations used to define the legal status of the regions, and also the relations between central and subnational (regional) levels in Scotland and Catalonia.